Bioinspired Self‐Healing Human–Machine Interactive Touch Pad with Pressure‐Sensitive Adhesiveness on Targeted Substrates. Issue 50 (10th November 2020) - Gao, Guorong; Yang, Fangjian; Zhou, Fenghua; He, Jiang; Lu, Wei; Xiao, Peng; Yan, Huizhen; Pan, Caofeng; Chen, Tao; Wang, Zhong Lin
Abstract: There is an increasing interest to develop a next generation of touch pads that require stretchability and biocompatibility to allow their integration with a human body, and even to mimic the self‐healing behavior with fast functionality recovery upon damage. However, most touch pads are developed based on stiff and brittle electrodes with the lack of the important nature of self‐healing. Polyzwitterion–clay nanocomposite hydrogels as a soft, stretchable, and transparent ionic conductor with transmittance of 98.8% and fracture strain beyond 1500% are developed, which can be used as a self‐healing human–machine interactive touch pad with pressure‐sensitive adhesiveness on target substrates. A surface‐capacitive touch system is adopted to sense a touched position. Finger positions are perceived during both point‐by‐point touch and continuous moving. Hydrogel touch pads are adhered to curved or flat insulators, with the high‐resolution and self‐healable input functions demonstrated by drawing, writing, and playing electronic games. Abstract : There is an increasing interest to develop the next generation of touch pads, requiring stretchability, biocompatibility, and self‐healing, to allow integration with the human body. As a stretchable and transparent ionic conductor, polyzwitterion–clay nanocomposite hydrogels are developed as human–machine interactive touch pads with pressure‐sensitive adhesiveness on target substrates with high‐resolution and self‐healable input functions demonstrated by drawing, writing, and playing electronic games.